If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4g + -2)(4g + -2) = 4 Reorder the terms: (-2 + 4g)(4g + -2) = 4 Reorder the terms: (-2 + 4g)(-2 + 4g) = 4 Multiply (-2 + 4g) * (-2 + 4g) (-2(-2 + 4g) + 4g * (-2 + 4g)) = 4 ((-2 * -2 + 4g * -2) + 4g * (-2 + 4g)) = 4 ((4 + -8g) + 4g * (-2 + 4g)) = 4 (4 + -8g + (-2 * 4g + 4g * 4g)) = 4 (4 + -8g + (-8g + 16g2)) = 4 Combine like terms: -8g + -8g = -16g (4 + -16g + 16g2) = 4 Add '-4' to each side of the equation. 4 + -16g + -4 + 16g2 = 4 + -4 Reorder the terms: 4 + -4 + -16g + 16g2 = 4 + -4 Combine like terms: 4 + -4 = 0 0 + -16g + 16g2 = 4 + -4 -16g + 16g2 = 4 + -4 Combine like terms: 4 + -4 = 0 -16g + 16g2 = 0 Solving -16g + 16g2 = 0 Solving for variable 'g'. Factor out the Greatest Common Factor (GCF), '16g'. 16g(-1 + g) = 0 Ignore the factor 16.Subproblem 1
Set the factor 'g' equal to zero and attempt to solve: Simplifying g = 0 Solving g = 0 Move all terms containing g to the left, all other terms to the right. Simplifying g = 0Subproblem 2
Set the factor '(-1 + g)' equal to zero and attempt to solve: Simplifying -1 + g = 0 Solving -1 + g = 0 Move all terms containing g to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + g = 0 + 1 Combine like terms: -1 + 1 = 0 0 + g = 0 + 1 g = 0 + 1 Combine like terms: 0 + 1 = 1 g = 1 Simplifying g = 1Solution
g = {0, 1}
| 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 | | cos7x=cosx/3 | | 11-4+(-1)*5= | | 9t+18-3t-15= | | y=2x^4-4x^2+15 | | 2(2x-1)-3(x+3)=x+1 | | 7y+8y-3x-4x= | | 2x-25+7x-75=7x-20 | | 7x-x^3=6 | | 9x+3y-6x+2y= | | 4w+10=-3(w-8) | | 25x+7x-4x-6x= | | Sinx=-.72 | | 2(d+6)=-2d-12 | | X+40+y=180 | | 2x+33=7x+3 | | 0.84xa=1 | | X^2-(1+3i)x-2+2i=0 | | 5+3(2a-5)-(a-6)= | | 5X+20y=345 | | 16x^2-96x+25y^2=256 | | 3x+20y=345 | | x+.07x=7.49 | | 4y-18=18 | | 15a-9a=72 | | n^3-m^3x^3/n-mx | | .025x=46 | | .025x=100 | | x=0.9x+3 |